The Effects of Institutions on the Labour Market Outcomes: Cross-country Analysis - Yong-seong Kim; Taebong Kim (KDI Journal of Economic Policy, 2017)
This paper re-examines the impacts an institutional arrangement may have on labour market outcomes such as the employment and unemployment rates. Based on the results from a generalized econometric model, the generosity of unemployment insurance benefits, organized labour and active labour market policy have effects on a labour market in line with previous findings. However, taxes on labour and the degree of employment protection are found to affect neither the employment rate nor the unemployment rate. Thus, some findings in this paper validate earlier findings, whereas others do not.
Keywords: C01; J08; J21; P51; 330; Employment Rate; Unemployment Rate; Labor Market Institutions; Cross-country Analysis